Determinants of Crop Diversification in Bangladesh: An Econometric Analysis. Issue 2 (December 2021) - Azad, Abul Kalam
This study aims to investigate the factors that influence household behaviour in cultivating the diversified crops on their cultivable land in Bangladesh. Cragg's alternative tobit model has been applied to a unique rural household level dataset to find the catalysts of crop diversification. The results obtained portrayed a mixed impression of crop diversification in the country. The estimated results have revealed that the male head of household, the accessibility of information, a greater number of farming parcels and the availability of hired labour seem to govern the decision of a farming household to participate in non-rice crop production, while factors such as the total amount of land, agricultural extension service and irrigation facilities influence rice cultivation. Moreover, the findings obtained from the same Cragg's alternative tobit model estimation for the Aman, Boro and Aus seasons have also revealed a similar depiction of crop diversification in Bangladesh.